Advances in group processes. Vol. 17 - Shane R. Thye; Edward J. Lawler (Advances in group processes., 2000)
Advances in Group Processes publishes theoretical analyses, reviews, and theory-based empirical chapters on group phenomena. The series adopts a broad conception of 'group processes', including work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, justice, influence, decision making, intergroup relations, and social networks. This volume covers a broad section of theory and research. The first two chapters address stereotyping and discrimination, emphasizing the importance of intergroup relations in the production of seemingly intrapersonal phenomena. Themes of other chapters include: theoretical issues concerning status in task groups; aspects of power in bargaining and exchange; conflict in familial relations; the spread or transition of social phenomena; and the relations between micro-, meso-, and macro-level forces in sociological theorizing.